Structural and Functional Alterations in the Contralesional Medial Temporal Lobe in Glioma Patients - Yuan, Taoyang; Zuo, Zhentao; Ying, Jianyou; Jin, Lu; Kang, Jie; Gui, Songbai; Wang, Rui; Li, Chuzhong (Frontiers in Neuroscience, 2020)
Background: The human brain has an extraordinary ability to functionally change or reorganize its structure in response to disease. The aim of this study is to assess the structural and functional plasticity of contralesional medial temporal lobe (MTL) in the patients with unilateral MTL glioma. Methods: 68 patients with unilateral MTL glioma (Left MTL glioma, n = 33; Right MTL glioma, n = 35) and 40 healthy controls were recruited and scanned with 3D T1 and rest-fMRI. We explored the structural of contralesional MTL with Voxel-based morphometry (VBM) and memory network of contralesional hemisphere using resting-state functional connectivity (rs-FC). The association between FC and cognitive function was assessed with partial correlation. Results: Compared with healthy controls, both patient groups exhibited 1) a large cluster of voxels with gray matter volume decrease in contralesional MTL using region of interest (ROI)–based VBM analysis (Cluster level p < 0.05, FDR corrected); 2) decreased intra-hemispheric FC between posterior hippocampus and posterior cingulate cortex (p < 0.01, Bonferroni corrected). Intra-hemispheric FC between posterior hippocampus and posterior cingulate cortex was positively correlated with cognitive function in both patient groups. Conclusions: Using multiple-modality brain imaging tools, we found structural and functional alteration of the contralesional MTL in patients with unilateral MTL glioma. These findings suggest contralesional cortex can present decompensation of structure and function in the patients with unilateral glioma, except compensatory structural and functional adaptation. Our study provided additional insight into neuroanatomical and functional changes of contralesional cortex in the patients with glioma.